Answer:
m∠1°= 75°
m∠2°= 105°
Step-by-step explanation:
It's on edg.
Answer:
(7, 5)
Step-by-step explanation:
When reflecting over the x-axis, the only position that moves is the y-coordinate as it is going above the axis it was previously below. Since point F's original position was (7, -5) it is 5 spaces away from the x-axis. We move 5 places up to be even with the x-axis, then move up another 5 places to reflect the point to get F'.
Hope this Helps!
Step-by-step explanation:
Use SOH-CAH-TOA.
Sine = Opposite / Hypotenuse
Cosine = Adjacent / Hypotenuse
Tangent = Opposite / Adjacent
Let's start with #12. The hypotenuse is 18. The side adjacent to ∠B is 6. Since we have the adjacent side and hypotenuse, we should use cosine.
cos B = 6/18
Solving for B:
B = cos⁻¹(6/18)
Using a calculator:
B ≈ 70.5°
Now let's do #14. The side adjacent to ∠B is 19, and the side opposite of ∠B is 22. Since we have the adjacent side and opposite side, we should use tangent.
tan B = 22/19
Solving for B:
B = tan⁻¹(22/19)
Using a calculator:
B ≈ 49.2°
Answer:
5
Step-by-step explanation:
5÷5x and 25÷5
1 × 5
your answer is 5
<u>Answer:</u>
The solution set of given equations -x-y-z = -8 and - 4x + 4y + 5z = 7 and 2x + 2z = 4 is (3, 6, -1)
<u>Solution:</u>
Given, set linear equations are
-x – y – z = -8 ⇒ x + y + z = 8 → (1)
-4x + 4y + 5z = 7 ⇒ 4x – 4y – 5z = -7 → (2)
2x + 2z = 4 ⇒ x + z = 2 → (3)
We have to solve the above given equations using substitution method.
Now take (3), x + z = 2 ⇒ x = 2 – z
So substitute x value in (1)
(1) ⇒ (2 – z) + y + z = 8 ⇒ 2 + y + z – z = 8 ⇒ y + 0 = 8 – 2 ⇒ y = 6.
Now substitute x and y values in (2)
(2) ⇒ 4(2 – z) – 4(6) – 5z = - 7 ⇒ 8 – 4z – 24 – 5z = -7 ⇒ -9z – 16 = -7 ⇒ 9z = 7 – 16 ⇒ 9z = -9 ⇒ z = -1
Now substitute z value in (3)
(3) ⇒ x – 1 = 2 ⇒ x = 2 + 1 ⇒ x = 3
Hence, the solution set of given equations is (3, 6, -1).